2018
DOI: 10.1088/2057-1976/aab524
|View full text |Cite
|
Sign up to set email alerts
|

SelenizedSaccharomyces cerevisiaecells are a green dispenser of nanoparticles

Abstract: Selenized Saccharomyces cerevisiae cells are used as a nutritional supplement for humans and animals since they contain large amounts of selenomethionine. Although it has been discussed less frequently, they also have a considerable quantity of selenium nanoparticles (Se-NP). Se-NP were generated inside cells after 48 h of incubation with sodium selenite; these nanoparticles were shown to have a spherical morphology, with an estimated size of 20-30 nm, and were mainly made up of Se. The type of Se-NP produced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 42 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…In the present study, SeITE02 cells cultured under metabolically controlled conditions were characterized by a massive presence of MVs (Figures 2, 3), which were observed to surround the SeNPs (Figures 2D, 3C). These observations suggested that SeNPs expulsion might occur through a vesicular-mediated process, as proposed for Rhodospirillum rubrum (Kessi and Hanselmann, 2004) and Saccharomyces cerevisiae (Zhang et al, 2012; Pereira et al, 2018). Moreover, at the early stage of SeITE02 growth on glucose, EPS-like material was detected (Figure 2A), which represents a strategy adopted by bacteria to counteract the toxicity exerted by metal cations or metalloid oxyanions, due to the adsorptive potential of these biological exudates (Jixian et al, 2015; Zheng-Bo et al, 2015).…”
Section: Discussionmentioning
confidence: 72%
“…In the present study, SeITE02 cells cultured under metabolically controlled conditions were characterized by a massive presence of MVs (Figures 2, 3), which were observed to surround the SeNPs (Figures 2D, 3C). These observations suggested that SeNPs expulsion might occur through a vesicular-mediated process, as proposed for Rhodospirillum rubrum (Kessi and Hanselmann, 2004) and Saccharomyces cerevisiae (Zhang et al, 2012; Pereira et al, 2018). Moreover, at the early stage of SeITE02 growth on glucose, EPS-like material was detected (Figure 2A), which represents a strategy adopted by bacteria to counteract the toxicity exerted by metal cations or metalloid oxyanions, due to the adsorptive potential of these biological exudates (Jixian et al, 2015; Zheng-Bo et al, 2015).…”
Section: Discussionmentioning
confidence: 72%
“…This transformation was reported to be induced by reductase enzymes [ 7 ]. It was observed that the addition of a protein synthesis inhibitor during the culture of yeast cells with Se IV led to the inhibition of the synthesis of Se 0 [ 33 ]. The authors also studied the possibility of generating Se 0 during the fermentation of yeast and found a significant reduction of the transformation of Se IV into Se 0 at cold temperatures.…”
Section: Quantification Of Elemental Se (Se 0 ) In...mentioning
confidence: 99%
“…However, it should be pointed out that those studies only analyzed the water-soluble fraction of SY, and Se 0 was not detected because it is a water-insoluble species. Elemental Se is also an iSe that has already been detected [ 19 , 33 , 49 , 50 ], but its accurate quantification in SY has not been possible until recently [ 20 ]. The presence of a significant quantity of Se 0 , and consequently of iSe, helps to explain the bio-efficacy results of SY when used as a feed additive [ 3 ].…”
Section: The Proportion Of Inorganic and Organic Se In Symentioning
confidence: 99%
“…9 The yeast Saccharomyces cerevisiae oen serves as a source of biogenic SeNPs allowing synthesis in a broad size range which can be modulated by the concentration of the Se source in the medium and the time of incubation. 10,11 From the above discussion it is clear that there is an urgent need for reliable methods for the determination of selenium nanoparticles (SeNPs) in complex organic matrices; this comes from growing interest in SeNPs both as novel selenium supplements and also from a demand from regulatory bodies requiring detailed control of their presence in "organic selenium" food and feed supplements derived from plants and microorganisms. In this context selenium enriched yeast is a particularly suitable model sample for the development of analytical methodologies being, at the same time, (i) an organism able to effectively produce SeNPs and also (ii) used as a basis for purely organic (thus, theoretically, not containing SeNPs) food and feed supplements.…”
Section: Introductionmentioning
confidence: 99%
“…9 The yeast Saccharomyces cerevisiae often serves as a source of biogenic SeNPs allowing synthesis in a broad size range which can be modulated by the concentration of the Se source in the medium and the time of incubation. 10,11…”
Section: Introductionmentioning
confidence: 99%